The use of virtual reality as a perspective-taking manipulation to improve self-awareness in Alzheimer’s disease - Latgé-Tovar, Sofia; Bertrand, Elodie; Piolino, Pascale; Mograbi, Daniel C. (Frontiers in Aging Neuroscience, 2024)
We would like to submit the revised version of the article entitled "The use of virtual reality as a perspective-taking manipulation to improve self-awareness in Alzheimer's Disease" for publication in the article collection "To Know or Not to Know: Causes and Evolution of Lack of Awareness of Cognitive Decline in Neurodegenerative Diseases, Volume II" of Frontiers in Aging Neuroscience. Lack of awareness of disease, referred to as anosognosia, is a common feature of Alzheimer's disease (AD) and there is increasing evidence that the perspective through which information is presented may moderate the appraisal of performances. Considering the approaches aiming to investigate the lack of awareness, there is a scarcity of methods with ecological validity and that consider awareness as a heterogeneous phenomenon. The current study addressed the effect of perspective-taking on awareness and virtual reality as a promising tool for a greater evaluation of perspective-taking and awareness of condition, symptoms or cognitive ability. The paper also presented the clinical implications of the proposed tool for individualized assessments, highlighting the impacts on subjects' life and possible improvements in their awareness.